Detachable coils and glue embolization for hemoptysis secondary to anomalous systemic arterial supply to the left lower lobe: a case report and literature review - Congqing Xie; Congqing Xie; Gaoyi Li; Wei Wei; Weiming Wang; Bin Yang; Xun Zhang; Wei Hu; Yanneng Xu; Guangyan Si; Gang Yuan (Frontiers in Medicine)
Anomalous systemic arterial supply to the left lower lobe (ASALLL) is a rare congenital vascular malformation. It predominantly occurs in young and middle-aged adults, often presenting with recurrent hemoptysis of unknown etiology. The condition has a high clinical misdiagnosis rate, and its optimal treatment remains controversial. Traditional management involves surgical or thoracoscopic lobectomy with ligation of the anomalous artery. In recent years, with advancements in endovascular techniques, transcatheter arterial embolization (TAE) has gained increasing preference among patients due to its minimally invasive and highly effective nature. Previous cases have primarily employed coils or vascular plugs to occlude the anomalous artery, with no reported use of detachable coil combined with medical tissue glue for embolization. Here, we present the case of an 18-year-old male with hemoptysis, diagnosed with ASALLL via CTA, who underwent successful embolization of the anomalous systemic artery using detachable coils combined with medical tissue glue. The procedure was uneventful, with excellent postoperative recovery. At the 1-year follow-up, the patient remained asymptomatic, with no complications such as pulmonary necrosis or infection. We also reviewed recent literature on the diagnosis and management of this condition, discussing key points in its diagnosis and differential diagnosis, and comparing the advantages and disadvantages of surgical intervention versus TAE. It aims to provide more robust evidence for the accurate diagnosis and optimal treatment selection of this rare vascular anomaly.